p53-Dependent Anti-Proliferative and Pro-Apoptotic Effects of a Gold(I) N-Heterocyclic Carbene (NHC) Complex in Colorectal Cancer Cells - Dabiri, Yasamin; Abu el Maaty, Mohamed A.; Chan, Hoi Yin; Wölker, Jessica; Ott, Ingo; Wölfl, Stefan; Cheng, Xinlai (Frontiers in Oncology, 2019)
The tumor suppressor p53 has a diverse mutational profile in human malignancies, which is known to influence the potency of various chemotherapeutics, such as platins and anti-metabolites. However, the impact of the mutations in the TP53 gene (coding for p53) on the anti-cancer efficacy of gold complexes remains incompletely understood. We therefore investigated the anti-tumor properties of a gold(I) N-heterocyclic carbene (NHC) complex–termed MC3–in human colorectal cancer (CRC) cell lines encompassing three different p53 variations: HCT116 wild-type (WT), HCT116 p53−/−, and HT-29 (mutant; R273H). MC3 treatment induced intracellular reactive oxygen species (ROS) levels, and p21 expression, leading to cell cycle arrest in all cell lines, regardless of their p53 status. The pro-apoptotic response, however, was found to occur in a p53-dependent manner, with WT p53 harboring cells showing the highest responsiveness. Additionally, p73, which was speculated to substitute p53 in p53-deficient cells, was found to be markedly reduced with MC3 treatment in all the cell lines and knocking down its levels did not impact MC3's anti-tumor effects in HCT116 p53−/− cells. Collectively, our results suggest that this small molecule has anti-cancer properties in the context of deficient or mutant p53 and may therefore have chemotherapeutic potential for clinical application.